Risk factors and outcome differences in hypoglycaemia‐related hospital admissions: A case‐control study in England. Issue 10 (21st April 2017) - Zaccardi, Francesco; Webb, David R.; Davies, Melanie J.; Dhalwani, Nafeesa N.; Housley, Gemma; Shaw, Dominic; Hatton, James W.; Khunti, Kamlesh
Abstract : Aims: To evaluate risk factors for hospital admissions for hypoglycaemia and compare length of hospitalization, inpatient mortality and hospital readmission between hypoglycaemia‐ and non‐hypoglycaemia‐related admissions. Materials and methods: We used all admissions for hypoglycaemia in individuals with diabetes to English NHS hospital trusts between 2005 and 2014 (101 475 case admissions) and 3 random admissions per case in individuals with diabetes without hypoglycaemia (304 425 control admissions). Risk factors and differences in the 3 outcomes were estimated with logistic and negative binomial regressions. Results: A U‐shaped relationship between age and risk of admission for hypoglycaemia was observed until the age of 85 years; compared to the nadir at 60 years, the risk was progressively higher in younger and older patients and steadily declined after 85 years. Social deprivation (positively) and comorbidities (negatively) were associated with the risk of admission for hypoglycaemia. Compared to Caucasians, other ethnic groups had lower (Bangladeshi, Pakistani, Indians) or higher (Caribbean) risk of admission for hypoglycaemia. Length of hospitalization was 26% shorter while risk of rehospitalization was 65% higher in individuals admitted for hypoglycaemia. Compared to admissions for hypoglycaemia, risk of inpatient mortality was 50% lower for unstable angina but higher for acute myocardial infarction (3 times), acute renal failure (5 times) or pneumonia (8 times). Conclusions: Among hospital‐admitted individuals with diabetes, age, social deprivation, comorbidities and ethnicity are associated with higher frequency of hospitalization for hypoglycaemia. Admission for hypoglycaemia is associated with a greater risk of readmission, a shorter length of hospitalisation and a generally lower inpatient mortality compared to admissions for other medical conditions. These results could help in identifying at‐risk groups to reduce the burden of hospitalization for hypoglycaemia.